New Cohesion Policy of the European Union in Poland How It Will Influence the Investment Attractiveness of Regions in 2014-2020 - Ambroziak, Adam A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The main objective of the book is to identify and evaluate the major changes in the Cohesion Policy of the European Union and their effects on Polish regions for the period of 2014-2020. The reader will learn how these changes result from the successful agreement on the Multiannual Financial Framework and implementation of the Europe 2020 strategy. Based on these aspects, the authors describe the main change in the Cohesion Policy of the EU, which is the renewed focus on competitiveness and skills to compete within the EU internal and the global market. The territorial approach taken by the EU with respect to entrepreneurial competitiveness is directly linked to the location attractiveness of regions.The authors argue that the new paradigm of the EU's Cohesion Policy will strengthen the focus on location attractiveness. To illustrate this case, they analyze Poland as one of the most appropriate and relevant Member States to evaluate the new rules underlying EU policies for 2014-2020, as Poland is the largest net-beneficiary of the EU budget.
Keywords: European Economic Community literature; Economic policy; Environmental economics; Regional economics; Spatial economics; Economics; European Integration; Regional/Spatial Science; Economic Policy; R & D/Technology Policy; Environmental Economics; Electronic books